DETECTION OF P16INK4A IN ORAL CAVITY AND OROPHARYNGEAL SQUAMOUS CELL CARCINOMA - Premalatha, Dr. S.; Kumar, Dr. I.Vijay Sathish; Ravi, Dr. S.; Raj Suresh, Dr. M. John; Sasikala, Dr. S.; Mohan, Dr. K.R. (International Journal of Innovative Research in Medical Science, 2016)
The incidence of HPV associated Head and Neck Squamous Cell Carcinoma (HNSCC) is increasing over the past 30 years. It is a growing public health concern. It has been reported that tissues of HPV associated HNSCCs over express p16INK4a. Therefore p16INK4a is used as a surrogate marker to detect HPV associated HNSCC. Immunohistochemical detection of p16INK4a is an easy and simple technique than molecular detection of HPVs. Hence we investigated the presence of p16INK4a in Oral and Oropharyngeal Squamous Cell Carcinoma (OPSCC). Aims: The objectives of our study are (1)To study the association of p16INK4a expression with OPSCC, thus with the HPV. (2) To compare the p16INK4a expression in oral cavity and oropharyngeal SCC. (3) To correlate the level of p16INK4a expression with different grades of OPSCC. Methods: A total sample of 35 cases were analysed during the period of June 2014 to August 2015. We performed IHC in sections of formalin fixed paraffin embedded tissue of OPSCC cases and correlated the various patterns of p16INK4a positivity with respect to histopathological diagnosis. Results: In the present study, 71.43% of the OPSCC cases were above 50 years of age. OPSCC was more common in males with male to female ratio of 8:1. 94.29% of OPSCC cases were positive for p16INK4a, of which the most common pattern was diffuse nuclear and cytoplasmic staining (37.14%). Conclusion: In the present study, increased number of OPSCC cases were seen over expressing p16INK4a (94.29%). Oropharynx was the commonest site for p16INK4a positivity (94.44%). Among the oral cavity SCC cases, tongue was the most common site involved (64%). Of the OPSCC cases, most cases (37.14%) had diffuse pattern of p16INK4a over expression. However, DNA detection based studies are needed to validate the utility of IHC detection of p16INK4a as a surrogate marker for HPV associated HNSCC.